Comparison of the Effectiveness Between Conventional and Modified Cinch Suture Techniques in LeFort I Osteotomy: A Systematic Review and Meta-Analysis of Randomized Control Trials. (18th April 2023) - Yang, Jia-Ruei; Chu, Yu-Ying; Liao, Han-Tsung; Lee, Che-Hsiung
Abstract : Background: LeFort I osteotomy changes the morphology of the nose. The cinch suture has been proven to prevent the increase in nasal base and alar width. Different types of cinch sutures have been proposed. However, their effectiveness is unclear. Aim and Objectives: The aim of this study was to compare the surgical outcomes between conventional and modified cinch techniques through a systematic review and meta-analysis of randomized control trials (RCTs). Material and Methods: We performed systematic search from Embase, PubMed, and the Cochrane Library according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement up to March 2021. The surgical techniques of different cinch sutures were reviewed, and the outcomes of nasal alar width and alar base width were compared between modified and conventional methods. Results: A total of 4 eligible RCTs were included in this meta-analysis. Pooled data showed no significant difference in alar base width change between modified and conventional methods (mean difference, −0.37; 95% confidence interval, −1.32 to 0.57; P = 0.44). Pooled data of 3 studies also showed no significant difference in nasal alar width change (mean difference, −0.11; 95% confidence interval, −1.18 to 0.95; P = 0.83). Conclusion: Based on the current data pooled from the available RCTs, no significant difference was found between the conventional cinch technique and the modified technique.